Techniques of NLP that Improve Effectiveness IN AN English Language Classroom - Menon, Shalini; M. , Nagalakshmi (International Journal of Psychosocial Rehabilitation, 2020)
The establishment of English as a universal language has mandated people’s adeptness in the usage of the language in manifold ways. Today, the role of English language classrooms is not merely teaching the components of grammar and rules and regulations alone. One has to understand the insecurities and fear of failure in students that have to be rightly catered to. When this learning dawns, one knows that a psychological approach is pertinent to derive desired results NLP, known for its ability to alter negative belief patterns and instill confidence in learners, is thus seen as an effective tool to handle such issues in a classroom. The paper elaborates how the techniques of NLP can be used to create a good teacher-student rapport, thus increasing the effectiveness in a language classroom.